A Case Report of Tinea Capitis in Children: Utility of Trichoscopy - Harningtyas, Citra Dwi; Ervianti, Evy; Astari, Linda; Anggraeni, Sylvia; Yuri Widia (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Tinea capitis (TC) is the most prevalent pediatric superficial dermatophyte infection. Scalp dermoscopy or